PLANEAMIENTO ESTRATÉGICO CON BSC EN UN MODELO DE EXCELENCIA EN LA EMPRESA TEXTIL HAKENI Y MEJORA CONTINUA - Huamán Mejía, María Celina (2011)
The study presents a Design Report with BSC Strategic Planning in a model of Excellence in Textile Enterprise Hakeni and continuous improvement, business excellence, interaction with the environment and internationalization deployed on a set of indicators of learning, process management, customers, market and finance is directly related to the continuous improvement of the company, shows a very accurate information in the context of a model of excellence and that from the organizational profile identifies the strategic challenges in the Plan. The Strategic Plan has strategic elements for BSC implementation and monitoring such as: A strategic mapping four perspectives, four projects or initiatives: a) Project management of implementation processes, b) implementation and project management skills, project Marketing plan and Project implementation information System each with an impact on the development of the company. The study shows that continuous improvement is demonstrated in the management with new tools designed to measure, outlined tool according to the needs and characteristics of the company Hakeni.